Functional Reintegration of Sensory Neurons and Transitional Dendritic Reduction of Mitral/Tufted Cells during Injury-Induced Recovery of the Larval Xenopus Olfactory Circuit - Hawkins, Sara J.; Weiss, Lukas; Offner, Thomas; Dittrich, Katarina; Hassenklöver, Thomas; Manzini, Ivan (Frontiers in Cellular Neuroscience, 2017)
Understanding the mechanisms involved in maintaining lifelong neurogenesis has a clear biological and clinical interest. In the present study, we performed olfactory nerve transection on larval Xenopus to induce severe damage to the olfactory circuitry. We surveyed the timing of the degeneration, subsequent rewiring and functional regeneration of the olfactory system following injury. A range of structural labeling techniques and functional calcium imaging were performed on both tissue slices and whole brain preparations. Cell death of olfactory receptor neurons and proliferation of stem cells in the olfactory epithelium were immediately increased following lesion. New olfactory receptor neurons repopulated the olfactory epithelium and once again showed functional responses to natural odorants within one week after transection. Reinnervation of the olfactory bulb by newly formed olfactory receptor neuron axons also began at this time. Additionally, we observed a temporary increase in cell death in the olfactory bulb and a subsequent loss in olfactory bulb volume. Mitral/tufted cells, the second order neurons of the olfactory system, largely survived, but transiently lost dendritic tuft complexity. The first odorant-induced responses in the olfactory bulb were observed three weeks after nerve transection and the olfactory network showed signs of major recovery, both structurally and functionally, after seven weeks.